AN INSIGHT INTO SOCIETY THROUGH KALIVIḌAMBANA - Devi, Arpana (International Journal of Research -GRANTHAALAYAH, 2025)
The Kaliviḍambana or the ‘Mockery of the Kali Age’ is a wonderful work of Nīlakaṭḥhadīkṣita. Nīlakaṇṭhadīkṣita occupies a high position among the galaxy of Indian writers of eminence. In the work, a realistic picture of the society is met with. In the work, the author criticizes the immoralities prevailing in the Kali (present) age. The poet observed that different professionals of his time used fraud and deception in their professions. He depicts a degenerated society where people lead an immoral life. The poet uses satiric humour to expose hypocrisy prevailing in the society. The work attracts the attention of the readers due to its amazing insights about the society presented with lively humour.